Fishery, diet composition and reproductive biology of the dolphinfish Coryphaena hippurus (Linnaeus, 1758) off Karnataka, south-west coast of India - Rajesh, K. M.; Rohit, Prathibha; Abdussamad, E. M. (Indian Journal of Fisheries, 2016)
Fishery, diet composition and reproductive biology of the dolphinfish Coryphaena hippurus (Linnaeus, 1758) landed along Karnataka Coast during 2013-15 were studied. The estimated average landing of the species in India during the study period was 7975 t of which Karnataka contributed 2.73% (218 t). The fish is mainly exploited by gillnet and also by troll lines operated from trawlers. A few stray specimens were also landed by purse seines. The fork length (FL) was in the range of 32-128 cm and fishes in the length range (FL) of 55-90 cm dominated the catch, contributing 79.8% of the total landings. The most dominant prey item, in terms of occurrence (70.57%) and weight (83.18%) were finfishes followed by cephalopods (19.62% by occurrence and 13.66% by weight) and crustaceans (7.01% occurrence and 1.32% by weight). The index of relative importance (IRI ) values were 85.3, 13.39 and 0.68% respectively for fish, cephalopods and crustaceans respectively. Sex ratio (1:2.05) indicated dominance of females in the fishery. Presence of mature and spent specimens throughout the year suggests that the species spawns all through the year. Peak spawning period was from June to September. This coincided with gradual increase in gonadosomatic index (GSI) values ahead of May which reached a peak during August-September.